HEARING LOSS AS AN INDICATOR OF CAROTID ARTERY STENOSIS: MECHANISMS, DIAGNOSIS, AND TREATMENT - Khaydarova G.S; Shodmonkulova G.R (TADQIQOTLAR, 2025)
Carotid artery stenosis (CAS) is an underrecognized contributor to sensorineural hearing loss (SNHL). The underlying vascular mechanisms and implications for stroke risk require further exploration. Objective:To summarize the prevalence, pathophysiology, diagnostic tools, and treatment options for CAS-related SNHL. Methods:A  review  of  current  literature,  including  epidemiological  data, vascular pathophysiology, imaging modalities, biomarkers, and emerging therapies. Results:Approximately  10–30%  of  CAS  patients  experience  SNHL  before major  cerebrovascular  events.  Inflammatory  pathways,  oxidative  stress,  and endothelial  dysfunction  contribute  to  cochlear  ischemia.  Advanced  imaging techniques, such as functional MRI and transcranial Doppler ultrasound, offer early detection of vascular-induced hearing loss. Pharmacologic interventions (vasodilators, antioxidants, statins) and cochlear implants may improve outcomes. Conclusion:Hearing loss may serve as an early biomarker for carotid disease. Routine audiometric screenings in high-risk populations could aid early intervention and  stroke  prevention.  Further  studies  are  needed  to  assess  the  impact  of  vascular interventions on hearing function.